Comparison of the Effects of Dovitinib and Bevacizumab on Reducing Neovascularization in an Experimental Rat Corneal Neovascularization Model. Issue 9 (September 2019) - Sahan, Berna; Ciftci, Ferda; Eyuboglu, Signem; Yaba, Aylin; Yilmaz, Bayram; Yalvac, Belkıs Ilgaz
Abstract : Purpose: To compare the inhibitory effects of dovitinib and bevacizumab for treatment of corneal neovascularization (CNV). Methods: Thirty-nine adult female Sprague Dawley rats weighing 180 to 250 g were used. CNV was induced by silver nitrate in the right eye of each rat. After the chemical burn, the animals were randomized into 5 groups. Group 1 did not receive any chemical substance. Group 2 received dimethyl sulfoxide, group 3 received bevacizumab 5 mg/mL, group 4 received dovitinib 5 mg/mL, and group 5 received bevacizumab 5 mg/mL + dovitinib 5 mg/mL topically administered twice daily for 14 days. On the 14th day, slit-lamp examination was performed, and anterior segment photographs were taken. The corneal neovascular area was measured on photographs as the percentage of the cornea's total area using computer imaging analysis. The corneal sections were stained with hematoxylin and eosin for histopathological examination. Results: A statistically significant decrease in the percentage of CNV was found in all treatment groups (group 3, group 4, and group 5) compared with the control group (group 1) ( P < 0.01). A statistically significant difference in the percentage of CNV was found among group 3, group 4, and group 5 ( P = 0.003). The percentage of CNV in group 4 was significantly higher than that in group 3 and group 5 ( P 1 = 0.004; P 2 = 0.006). There was no statistically significant difference in the percentage of CNV between group 3 and group 5 ( P = 0.228). Conclusions: Dovitinib is a newly developed multitargeted tyrosine kinase inhibitor. Topical administration of dovitinib effectively inhibited CNV, but this effect of dovitinib was found less than topical bevacizumab.